Indentation cracking and acoustic emission generation in silicon - Ong, Woon Eng. (2009)
This thesis is a summary of research work on the indentation fracture of silicon wafers. Crack formation on silicon and its fracture toughness were studied using single indentation at different loads. It is shown that indentations made at higher loads are more likely to produce lateral cracks and more pronounced radial cracks. The presence of a indentation size effect was also found when calculating the fracture toughness as a function of the indentation load and radial crack length.